Ambiguous Genitalia Associated with an Extremely Rare Syndrome: A Case Report of XLAG Syndrome and Review of the Literature - Brijnandan GUPTA; Prashant RAMTEKE; V K PAUL; Tarun KUMAR; Prasenjit DAS (Federation of Turkish Pathology Societies, 2019)
X-linked lissencephaly, absent corpus callosum, and epilepsy of neonatal onset with ambiguous genitalia comprises the XLAG syndrome and only 15 cases have been reported in literature. Due to its rarity, the exact clinical course and outcome are not known. Exact associations of this disease are also elusive. Hereby we are reporting this extremely rare entity and we searched the English literature extensively to get consolidated knowledge regarding this entity that would help the readers. Pre-natal radiological work-up can detect these malformations, which should be followed by medical termination, counseling and karyotyping. Till date the longest survival noted was 4 years only.